Impact of fuel prices on paddy farmer's expenditure allocation in Malaysia - Baharudin, Siti Aisyah; Mohamed Arshad, Fatimah; Muhammad Tasrif; Ibragimov, Abdulla (Panoply Consultancy, 2015)
The international price increase in fuel and food has direct impact on production cost and domestic prices. Fuel and fertilizers are agricultural inputs in paddy production. Fuel is needed for operating paddy machineries such as tractors and harvesters, while fertilizers are important for keeping the soil for paddy crop fertile. Increment in fuel prices will affect paddy productivity and farmer’s expenditure. Farmer’s expenditure includes fuel (petrol and diesel), input (fertilizer, pesticides and seed) and labour cost. (i) What is the current behaviour of paddy expenditure in 1990 to 2015? (ii) What is the future trend of farmer’s expenditure under the fuel price change in 2016 to 2030? (iii) How the farmer’s will decide to allocate their expenditure on inputs under the different world fuel price rate? The situation requires one to seek a methodology that could explain the complexity of the system and to establish an insight on the interrelation of the key variables. The system dynamics model provides a framework for understanding the impact of fuel price change on farmer’s expenditure. Simulation result show domestic fuel price will follow world’s crude oil price trend with the increasing by 40% in 2030 with the average of 3.8% per year. Meanwhile, expenditure of paddy increase by 3.8. However, the share of fuel and fertilizer is about 45% of the total expenditure as fuel price could indirectly affect the price of fertilizer. Indirect effect is greater than direct effect on farmer’s expenditure.